2020
DOI: 10.4102/ac.v20i1.872
|View full text |Cite
|
Sign up to set email alerts
|

Design thinking in entrepreneurship education: Understanding framing and placements of problems

Abstract: Orientation: Design thinking presented an alternative lens for entrepreneurship education.Research purpose: The purpose of this article was to illustrate (with a framework) the benefits of encouraging a design-based mindset when exploring problem placement and framing to create new opportunities for entrepreneurship students.Motivation for the study: The role of placement and framing of open-complex problems has not been fully embraced in the literature on design thinking for entrepreneurship education. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…References A hands-on, participative, collaborative approach Process-oriented model for entrepreneurship education User-driven and interdisciplinary Sarooghi et al, (2019) Facilitates meaning or mental connections between aspects of "what" learners know and "how to" implement or use this knowledge Promotes interdisciplinary projects that can broaden individual understanding of different perspectives Tselepis & Lavelle, (2020) Transforms ideas into concrete entities in the form of prototypes, sketches, or flowcharts Supporting and simplifying collaboration Promotes deep thought and reflection Biffi et al, (2017) Increased student motivation Real-world learning Lynch et al, (2021) From the above analysis, it can be concluded that design thinking offers a welcome approach to entrepreneurial education, mainly due to its focus on human needs, experimental learning, and interdisciplinary approach to problem-solving.…”
Section: Advantagesmentioning
confidence: 99%
“…References A hands-on, participative, collaborative approach Process-oriented model for entrepreneurship education User-driven and interdisciplinary Sarooghi et al, (2019) Facilitates meaning or mental connections between aspects of "what" learners know and "how to" implement or use this knowledge Promotes interdisciplinary projects that can broaden individual understanding of different perspectives Tselepis & Lavelle, (2020) Transforms ideas into concrete entities in the form of prototypes, sketches, or flowcharts Supporting and simplifying collaboration Promotes deep thought and reflection Biffi et al, (2017) Increased student motivation Real-world learning Lynch et al, (2021) From the above analysis, it can be concluded that design thinking offers a welcome approach to entrepreneurial education, mainly due to its focus on human needs, experimental learning, and interdisciplinary approach to problem-solving.…”
Section: Advantagesmentioning
confidence: 99%
“…Research methods procedure are currently addressed by increasing number of scientists from various scientific fields and industries (Cross, 2001;Chou, 2018;Garbuio, at. al., 2018;Kimbell, 2011;Tselepis & Lavelle, 2020).…”
Section: Objectmentioning
confidence: 99%
“…exemplary course designs (Nielsen & Stovang, 2015) or introducing new methods within this context (von Kortzfleisch et al, 2013). Some existing papers provide important initial ideas on the topic, but still remain insufficient by being published as solely conference proceedings (Huber et al, 2016;McLuskie & Dewitt, 2019;Tselepis & Lavelle, 2020).…”
Section: Existing Literature On the Dt/ee Nexusmentioning
confidence: 99%